SIRR AL-QADAR: MENYINGKAP RAHASIA TAKDIR DALAM ‘IRFAN IBN ‘ARABI - Ah Haris Fahrudi (MIYAH : Jurnal Studi Islam, 2022)
Abstract: One of the metaphysical problems that still provokes a long discussion, especially among philosophers and theologians, is the problem of God's knowledge of everything before creation occurs on the one hand and the recognition of man's freedom in doing his deeds. The obligation to believe in the destiny and freedom of choice of human beings as a condition for the implementation of Shari'a in Islamic discourse gave birth to a number of schools, namely Jabariyah, Qadariyah and the modern school of Ahlis sunnah. Although this issue has been discussed and debated for centuries, the fog of equality has not been exposed. That's because the postulates of both the Qur'an and the rational postulates seem to contradict each other. This article will discuss the contribution of Ibn 'Arabi, in untangling this issue, ie. Through what he claimed to be the knowledge of 'irfani Ibn Arabi sought to unravel the secret of destiny (sirr al-Qadar). In contrast to the average Sufi, who harbored exclusively this understanding of al-Qadar sirr, Ibn 'Arabi explained, though more of a gesture, this divine revelation is theoretically conceptual by insinuating the two concepts behind al-Qadar's sirr namely the concept of al-a'yan al-tabitah and the concept of al-'science of tabi' li al ma'lum. Through these two concepts Ibn 'Arabi hints at the aqidah of the sufis, for which there is no caliphate among them on this subject that there is no contradiction between the faith concerning Qadla' and the Qadar of Allah and the perfection of the nature of God especially his knowledge, iradah, masyia'ah and qudrah and man's freedom in doing. Ibn 'Arabi hereby dismissed the notion that sufis were of determinism or Jabariyah which was widely thought of them, nor Qadariyah. On the contrary sufi aqidah is in line with aqidah ahlissunnah wa al-jama'ah. Keyword: sirr al-Qadar, metaphysical, ‘irfani